An Assessment on Oxazolones-their Reactions and Applications - Aparna , Y. (Novel Aspects on Chemistry and Biochemistry Vol. 1, 2023)
This review attempts to present the prolific advance in recent years exclusively in the applications of oxazolones as preliminary materials for synthesis of betalactums, imidazolones, amino acids and utilization of oxazolones as photoswitches, thin films and polymer fibres. The classical Erlenmeyer synthesis of azlactones, which includes condensation of aldehydes with hippuric or aceturic acid in the presence of acetic anhydride and sodium acetate, is considered the most commonly used method for preparation of 2-oxazolin-5-ones. 2-oxazolin-5-ones are versatile compounds and are known to react at active bonding sites like C=N, C=O and C=C bonds. These contribute to numerous reactions such as replacement reactions, cycloadditions, and other types of reactions, as well as dimerization reactions, which lead to an increase in the variety of heterocyclic compounds.